Activos biológicos como propiedad, planta y equipo una revisión desde los criterios contemplados en la NIC 16 y la NIC 41 (2015)
The concept of biological assets and its financial performance, are important to the economy of Colombia part. Agricultural production is one of the main sectors of the economy, which is under the capitalist economic model supported by the processes of globalization and internationalization of markets. He research that led to this article involved the analysis of the International Accounting Standards and IAS 41 Agriculture and IAS 16 Property, Plant and Equipment, to obtain relevant information from companies in terms of decision making. It aims to analyze the criteria set international accounting standards for the recognition, measurement, presentation and disclosure of 1 Trabajo resultado de la investigación “Análisis de los activos biológicos desde las normas internacionales de contabilidad NIC 16 Propiedad, Planta y Equipo y el NIC 41 Agricultura” presentado como requisito de grado para optar al título de Contador Público en la Universidad del Quindío. El trabajo fue realizado bajo la modalidad de pasantía internacional realizada en la Universidad Tecnológica de Monterrey (México) en el año 2014. Artículo de Reflexión. 2 Estudiante X semestre de Contaduría Pública, Facultad de Ciencias Económicas y Administrativas, Universidad del Quindío. biological assets in the financial statements and changes regarding the traditional regulatory structure occurred in Colombia; from the analysis of the concepts of International Financial Reporting Standards IAS 16 and IAS 41 established for the treatment of biological assets. Therefore, the need for the amendment of national legislation in the agricultural sector. In order to enhance the financial and economic work in the companies, since they put the international forefront, something that obviously needs Colombia, by the non-recognition of biological assets.